Formal reasoning of knowledge in systems engineering through epistemic modal logic. Issue 1 (11th November 2020) - Kannan, Hanumanthrao
Abstract: Large‐scale systems engineering projects consist of hundreds to thousands of agents (stakeholders, managers, designers, etc.) spread across the organizational hierarchy. Each of these agents possesses knowledge in some form or the other, be it the knowledge of stakeholder needs, domain‐specific knowledge, knowledge of rules and regulations, knowledge gained from experience on previous projects, etc. It is important to formally represent this knowledge possessed by various agents in the systems engineering lifecycle, as this will enable knowledge reuse, reasoning capabilities, inferring new knowledge, and mitigate misinterpretation of knowledge as prevalent in document‐centric approaches. Such a formal representation will also help alleviate some of the challenges posed by the current document‐centric approaches concerning project delays and cost overruns in the development of large‐scale systems. This paper focuses on formally representing knowledge that exists in various phases of the systems engineering lifecycle by leveraging epistemic modal logic. Descriptive examples are used to demonstrate the practical reasoning capabilities of such a formal representation of knowledge in systems engineering projects.